2004
DOI: 10.1093/ps/83.7.1065
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Effective Caloric Value of Nonnutritive Factors: I. Pellet Quality and II. Prediction of Consequential Formulation Dead Zones

Abstract: Two experiments were conducted with male broilers to 1) establish a methodology for predicting effective caloric value (ECV), defined as dietary caloric density (CD) necessary for broilers to achieve specific BW and feed conversion ratio (FCR) combinations under standardized conditions and 2) quantify the ECV attributable to pellet quality (PQ), defined as the pellet to pellet fines ratio in the feeder. In experiment 1, chicks were reared to 56 d on diets varying in CD. Dietary caloric densities examined range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 23 publications
2
39
0
4
Order By: Relevance
“…Segundo Nir et al (1994) e Jensen (2001), a peletização reduz o gasto de energia das aves para mantença, aumentando a energia líquida de produção, portanto, há mais energia disponível para o ganho. A peletização favorece a eficiência de retenção da energia metabolizável aparente, o que justifica a melhor conversão alimentar das aves alimentadas com rações peletizadas ou trituradas (McKinney & Teeter, 2004;Lemme et al, 2006).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Segundo Nir et al (1994) e Jensen (2001), a peletização reduz o gasto de energia das aves para mantença, aumentando a energia líquida de produção, portanto, há mais energia disponível para o ganho. A peletização favorece a eficiência de retenção da energia metabolizável aparente, o que justifica a melhor conversão alimentar das aves alimentadas com rações peletizadas ou trituradas (McKinney & Teeter, 2004;Lemme et al, 2006).…”
Section: Resultsunclassified
“…Esse melhor desempenho tem sido associado ao aumento da digestibilidade dos nutrientes da ração (Moram, 1987;Zelenka, 2003) e ao aumento da densidade da ração, o que permite maior ingestão de nutrientes e, conseqüente-mente, maior taxa de crescimento (Toledo et al, 2001;Engberg et al, 2002;McKinney & Teeter, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…These results are similar to those reported by Nir et al (1995), Engberg et al (2002), Svihus et al (2004) and Cutlip et al (2008). These improvements have been variously attributed to increased nutritional density, increased nutrient intake, changes in the physical form of the feed, reduced feed wastage, decreased energy expenditure while eating (McKinney and Teeter, 2004;Skinner-Noble et al, 2005;Amerah et al, 2007;Cerrate et al, 2009;Yang et al, 2010), increased starch digestibility (Parsons et al, 2006), and improved apparent metabolisable energy (AME) and nutrient retention (Svihus et al, 2004;Adeyemi et al, 2008) mechanical action resulted in a rupture of the cell walls and thus made encapsulated nutrients of the feedstuff more accessible to digestive enzymes (Vande and Schrijver, 1988;Cutlip et al, 2008). Phytase and multienzymes plus phytase supplementation increased BW (3.3 and 4.6%) and BWG (3.7 and 4.9%), improved FCR (4.8 and 6.6%), and decreased feed intake by 1.6 and 2.2%, respectively, of the improvement in FCR as compared with those chicks fed a diet without enzyme supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, growth performance of broilers fed a crumble or pellet diet was better than those fed on mash feed (Jahan et al, 2006;Cutlip et al, 2008). Pelleting or crumbling improved nutrient digestibility, decreased feeding time, and was easier to eat (McKinney and Teeter, 2004;Skinner-Noble et al, 2005;Amerah et al, 2007;Cerrate et al, 2009;Yang et al, 2010;Attia et al, 2012). Jafarnejad et al (2010) reported that body weight (BW) and FCR were significantly improved in broilers fed crumble-pellet diets compared with those fed mash diets.…”
Section: Introductionmentioning
confidence: 99%